PENGEMBANGAN BAHAN AJAR ENERGI CAHAYA DAN ALAT OPTIK BERBASIS MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERLIBATAN DAN PEMAHAMAN KONSEP MAHASISWA UNIVERSITAS ALMUSLIM BIREUEN - Novi Sari Liani; Desy Sary Ayunda; Lissa Zikriana; Sharfina (LPPM Universitas Cipta Mandiri, 2025)
This study aims to develop teaching materials for basic elementary physics concepts based on the project-based learning model to increase student engagement and conceptual understanding at Umuslim Bireun and to test their feasibility. This study employed quantitative methods using the Research and Development (R&D) method. The ADDIE development model utilized analysis, design, development, implementation, and evaluation. The validation results from media experts indicated that the media aspects, technical quality, and media size achieved percentage values of 81.29%, 84.13%, and 89.02%, respectively, and were concluded as very good. The analysis by material experts clearly demonstrated that the media coverage, accuracy, currency, and arousal of interest achieved percentage values of 84.66%, 86.22%, 90.80%, 93.54%, and 91.47%, respectively, and were concluded as very good. The results of the analysis of linguists clearly show that in terms of clarity, suitability with student development and suitability with language rules with a presentation value of 88.45%, 89.77%, 92.39%. The results of the overall feasibility test for individual, group and field validation with a percentage of 89%, 87% and 92% of qualifications are very suitable. The results of the gain normality test analysis obtained results of 0.77 and 0.72 so that it can be concluded that there is an increase in the involvement and understanding of Umuslim students' concepts with light energy and optical tools teaching materials based on the project based learning model.